Evalution of Clinical and Sociodemograpic Features of Patients with Psoriasis in the Konya Region - Aykol, Caner; Mevlitoglu, Inci; Ozdemir, Mustafa; UNAL, MEHMET (My University, 2011)
Objective: Psoriasis is a chronic inflammatory dermatosis with silvery-white coloured squamas and is characterized by erythematous papules and plaques. Psoriasis is seen in 1-2% of the normal population. In this study we aim to introduce the clinical and demographic features of patients with psoriasis in our region.